Network traffic monitoring system based on embedded linux and single board computer - Md. Mostafijur Rahman (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2009)
This research describes the design and development of an Embedded Network Traffic Monitoring (ENTM) system based on single board computer (SBC) and an open source embedded Linux operating system (OS).